Predictive effects of big five personality traits on attitude to plagiarize / Ida Rosnita Ismail ... [et al.] - Ismail, Ida Rosnita; Abdul Hadi, Khairul Anuar; Md Pauzi, Suria Fadhillah; Zulkifli, Norsyazrah; Najid, Nurul Afzan (2012)
The objective of this study is to examine the predictive effects of five personality traits on attitude to plagiarize. Specifically, we hypothesized that conscientiousness, agreeableness, neuroticism, openness, and extroversion are predictors of attitude to plagiarize. Using survey questionnaire, data were collected form a convenience sample of 165 diploma students of UiTM Pahang. We used multiple linear regression to analyze the data. The results of this study show that only agreeableness and neuroticism were significant predictors to attitude to plagiarize.